Downregulation of ITGβ3 in colon adenocarcinoma reveals poor prognosis by affecting genome stability, cell cycle, and the tumor immune microenvironment - Zhao, Lei; Ma, Xiaoting; Li, Guangxin; Zhao, Pengfei; Lin, Haishan; Ma, Yingjie; Li, Huihui; Yu, Jing (Frontiers in Oncology, 2023)
Introduction Abnormal expression of integrin subunit beta 3 (ITGβ3), a gene-encoding protein, is related to the occurrence and development of cancers; however, the biological role of ITGβ3 in colon adenocarcinoma (COAD) remains unclear. Methods We used the Cancer Genome Atlas database to obtain the clinical data of patients with COAD, analyzed the mRNA gene clusters related to ITGβ3, and analyzed the interaction signal pathway and interaction protein network of the differentially expressed gene clusters. The results showed that ITGβ3 expression in COAD tumor tissues was significantly downregulated compared with that in paracancerous tissues. Low ITGβ3 expression in tumor tissues is associated with poor overall survival of patients with COAD. In multivariate analysis, stage IV and ITGβ3 low expression were independent prognostic factors. Gene Ontology analysis showed that differentially expressed genes (DEGs) were significantly enriched in leukocyte migration, cell adhesion, and extracellular matrix (ECM) organization. Kyoto Encyclopedia of Genes and Genomes analysis revealed that the DEGs were mainly enriched in ECM-receptor interactions, focal adhesion, and the PI3K-Akt signaling pathway. Protein-protein interaction network analysis revealed the hub and seed genes of the key modules related to ITGβ3. Finally, we analyzed the correlation between TGβ3 and immune-related genes and found that ITGβ3 expression was significantly correlated with tumor purity and infiltration level of dominant immune cells. Discussion These findings indicate that ITGβ3 downregulation in COAD may profoundly affect genome stability and multiple steps of the cell cycle, alter the tumor immune microenvironment, and be related to the prognosis of patients with COAD.